2019
DOI: 10.1186/s40661-019-0066-8
|View full text |Cite
|
Sign up to set email alerts
|

Preferences of women with epithelial ovarian cancer for aspects of genetic testing

Abstract: BackgroundAlthough genetic testing is recommended for women with epithelial ovarian cancer (EOC), little is known about patient preferences for various testing options. We measured relative preferences for attributes of testing in women with EOC referred for genetic counseling.MethodsSubjects were recruited to participate in a discrete-choice-experiment survey to elicit preferences for attributes of genetic testing: out-of-pocket cost ($0, $100, $250, or $1000), probability of a deleterious mutation (60, 80%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(37 citation statements)
references
References 19 publications
2
34
1
Order By: Relevance
“…Studies of patient-perceived value for money in genetic counselling are limited and this gap in knowledge represents an important area for future research. In women with ovarian cancer in whom genetic testing is recommended, the cost of testing was the most important factor, followed by probability of detecting a pathogenic variant, in 94 enrolled subjects recruited in a choice experiment survey of whom 68 (76.4%) presented for genetic counselling (Davidson et al, 2019). As current testing costs are now lower than those at the time this study was undertaken and some private patients are now eligible for Medicarefunded genetic testing, it could be hypothesized that satisfaction/perceived value would now be even higher.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of patient-perceived value for money in genetic counselling are limited and this gap in knowledge represents an important area for future research. In women with ovarian cancer in whom genetic testing is recommended, the cost of testing was the most important factor, followed by probability of detecting a pathogenic variant, in 94 enrolled subjects recruited in a choice experiment survey of whom 68 (76.4%) presented for genetic counselling (Davidson et al, 2019). As current testing costs are now lower than those at the time this study was undertaken and some private patients are now eligible for Medicarefunded genetic testing, it could be hypothesized that satisfaction/perceived value would now be even higher.…”
Section: Discussionmentioning
confidence: 99%
“…DCE studies generally performed better than CV in quality assessment, with only 1/17 (5.9%) [82] graded as low quality. Majority of the studies (10/17, 58.8%) [48,51,57,69,75,78,[83][84][85][86] were of high quality while 6/17 (35.3%) [49,50,53,65,72,74] were of moderate quality.…”
Section: Quality Assessmentmentioning
confidence: 91%
“…b Inclusive of 9 conference abstracts c Inclusive of 4 studies that did not clearly mention CV, but methodology is suggestive of CV d Total number of studies is more than 54 as some studies reported more than one outcome[ 39,42,44,48,50,63,81,82,84,85] …”
mentioning
confidence: 99%
“…For example, in clinics where the majority of cases are non-urgent, CA was found to be a useful tool for allowing patients to discuss their needs and choose medication, health service, and diagnostic tests that suit them the most [63,64]. In turn, CA constituted a supportive tool for clinicians to better understand patients' preferences and individualize their treatment plans [24,65,66]. Hence, the CA use in practice was suggested as a tool to effectively strengthen the communication between patients and healthcare professionals and to engage both parties in the shared decision-making process [12,62].…”
Section: Conjoint Analysis In Healthcarementioning
confidence: 99%